Rhodium(iii)-catalyzed annulative coupling between arenes and sulfoxonium ylides via C–H activation. Issue 6 (12th January 2018) - Zheng, Guangfan; Tian, Miaomiao; Xu, Youwei; Chen, Xiaohong; Li, Xingwei
Abstract : Sulfoxonium ylides acts as a bifunctional C2 -synthon in Rh(iii )-catalyzed redox-neutral annulative coupling with arenes for the synthesis of N-heterocycles and carbocycles. Abstract : The Rh(iii )-catalyzed annulative C–H functionalization of arenes with sulfoxonium ylides has been realized. Arenes assisted by diverse nucleophilic directing groups are viable substrates, and the coupling affords structurally diverse fused hetero- and carbocycles under redox-neutral conditions.